Análise de erros em questões de Geometria do ENEM : um estudo com alunos do Ensino Médio - Renato Rodrigues dos Santos (2014)
This research aims to analyze and classify the mistakes made by students from 3rd year high school, in solving questions of geometry of National High School Exam (ENEM), from five state Schools in Maringá. The research was sort of qualitative and developed in a single step by the application of a test with four questions extracted from previous exams of ENEM. The literature review lists the elements of: Geometry and its teaching, Curriculum Guidelines for Mathematics and Notebook Expectations Learning of State of Paraná, theory of errors and the ENEM. The results shown in this study indicate that the main mistakes made by students in solving questions of a Geometry are among the difficulties with questions interpretation, the passage of natural language to mathematical language and in application and formulas resolution. This corroborates with has been discussed in Mathematics Education about the importance of error analysis in mathematics teaching